UJI AKTIVITAS KRIM ANTI JERAWAT EKSTRAK ETANOL DAUN SEROJA (Nelumbo nucifera G.) TERHADAP BAKTERI Propionibacterium acnes DAN Staphylococcus aureus - Khairani Fitri; Tetty Noverita Khairani; Muhammad Andry; Nidia Rizka; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Lotus leaves (Nelumbo nucifera G.) is one of the plants that are potentially in the field of treatment, like antibacterial antiacne. Lotus leaves contain alkaloids, saponins, tannins, flavonoids and steroids are compounds of secondary metabolites in plants that are effective as an antibacterial. Objective; The study aimed to determine the antibacterial activity of lotus leaves ethanol extract against bacteria of Propionibacterium acnes and Staphylococcus aureus. Method; The ethanol extract of lotus leaves was made by maceration method using 96% ethanol as a solvent. The in-vitro antibacterial activity test used the well method with a concentration of 10%, 20% and 30%. Results; The results of the study with concentration of 10%, 20% and 30% have the inhibition zone on the bacteria Propionibacterium acnes where the concentration of 10% of 8.7mm, a concentration of 20% of 12.4mm and a concentration of 30% by 14.5mm. And the zone of inhibition on Staphylococcus aureus bacteria has a 10% concentration of 8.1mm, the concentration of 20% of 11.1mm and a concentration of 30% of 14.1mm. Concentration is the cream of the ethanol extract of the leaves of lotus at a concentration of 30%. Conclusion; The conclusion of this study showed that the ethanol extract of lotus leaves could be formulated in a cream dosage form and has antibacterial activity against Propionibacterium acnes and Staphylococcus aureus bacteria. It is suggested to the next researchers to do fractionation to get better dosage results.